Magnetic resonance imaging in neuromyelitis optica. - Tackley, G; Kuker, W; Palace, J (SAGE Publications, 2014)
Neuromyelitis optica (NMO), or Devic's disease, is a rare demyelinating disorder of the central nervous system that has a predilection for the optic nerve and spinal cord. Magnetic resonance imaging (MRI) is required to diagnose NMO. Longitudinally extensive transverse myelitis is NMO's imaging hallmark and the presence of a brain MRI that is not diagnostic of multiple sclerosis (MS) also remains part of the diagnostic criteria. It is increasingly recognised that MS and NMO brain imaging can, however, have similar appearances but differences do exist: hypothalamic, periaqueductal grey and area postrema lesions implicate NMO whilst cortical, U-fibre or Dawson's finger lesions are suggestive of MS. The timing of image acquisition, age, ethnicity and aquaporin-4 antibody status are all likely to alter the findings at MRI. This review therefore aims to overview and update the reader on NMO imaging, to provide clinically relevant guidance for diagnosing NMO and differentiating it from MS in order to guide management, and to highlight recent research insights.